CFD Analysis of a Non-newtonian Fluids Processing Pump. (November 2016) - Aldi, Nicola; Buratto, Carlo; Pinelli, Michele; Spina, Pier Ruggero; Suman, Alessio; Casari, Nicola
Abstract: Pumps are among the most spread machines in industrial facilities. In this work a comparative CFD analysis using different software is presented. The three-dimensional flow in the semi-open impeller and volute of a centrifugal pump is numerically simulated. The main advantage of semi-open impeller centrifugal pump is its efficiency which can be considered constant thanks to the clearance adjustment. In addition this kind of impeller is less likely to clog with solid bodies (important in case of slurry-processing). The open impeller has all the parts visible, so it is easier to inspect for wear and damages. Eventually it is lighter than a shrouded impeller: it can spin faster. The stress due to centrifugal force is indeed a limit for the speed of this machines. On the other hand its main disadvantage if compared to a shrouded pump is its lower efficiency due to the heavier tip leakage. In addition it cannot be employed in case of explosive products: the risk of contact between impeller and volute causing sparks is not negligible. The simulations have been carried out using both open-source and proprietary software: OpenFOAM®, PumpLinx ® and ANSYS-CFX ®. The performance of the machine handling both Newtonian and non-Newtonian fluids are also investigated. The numerical models and the results of the different computational strategies were compared with the experimental data and the accuracy of different software is evaluated in the case of Newtonian model. It is well known that the performance of a centrifugal pump drops processing a viscous fluid. Even so the behavior during the pumping of non-Newtonian fluids has not been investigated so far. The non-Newtonian fluid processed is a shear-thinning fluid (the apparent viscosity decreases with an increase stress). The slurries which are usually processed in the food industries, chemical plants and oil&gas processes show a usual behavior which correspond to this kind of model.